The Image Of IAIN Padangsidimpuan Among High Achievement Students (Educational Services Marketing Perspective) - Isa, Muhammad; Siregar, Budi Gautama (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2019)
The presence of students in a tertiary institution is an absolute requirement that must be met. IAIN Padangsidimpuan applies three different types of selection of new student candidates. These include the National Academic Achievement Selection (Seleksi Prestasi Akademik Nasional/SPAN - PTKIN), the State Islamic College Entrance Examination (Ujian  Masuk  Perguruan  Tinggi  Agama Islam Negeri/UM - PTKIN), and Independent Exams. SPAN - PTKIN is intended to recruit prospective new students from high achieving students. However, many prospective students who passed the SPAN-PTKIN pathway did not re-register again. This condition occurs almost every year. SPAN - PTKIN is intended to recruit prospective new students from high achieving students. However, many prospective students who passed the SPAN-PTKIN pathway did not re-register. This condition occurs almost every year. This has led to the presumption that there is a tendency for prospective new students from high achieving students through the SPAN-PTKIN pathway to have low interest in continuing education at the Padangsidimpuan IAIN. So it needs to be investigated how the actual image of IAIN Padangsidimpuan among high achieving students and other related aspects. This is important as input for improving the selection system for prospective new students or making decisions in the planning of promotion strategies for Padangsidimpuan IAIN in the future. This research is a descriptive quantitative research. The population of this study was all high achieving students at the State High School / Islamic High School level in Padangsidimpuan City. The main instrument was a questionnaire distributed to 220 respondents, which were selected by purposive sampling technique. Data analysis was performed by t-test and ANOVA. Data processing is done by SPSS software. From the results of data processing, it is known that the overall Iangs Padangsidimpuan imagery among Padangsidimpuan City achievers is included in the "good" category, with a value of 3,2353 from the maximum scale of 5. The t test results are known that, the Islamic High School students' point of view regarding the image of IAIN Padangsidimpuan is better than state school students. Therefore, it is necessary to do more frequent promotion to the state schools. From the ANOVA test results it is known that there is actually no difference in the image of the IAIN Padangsidimpuan between groups of respondents from different family classes. This indicates that IAIN Padangsidimpuan does not need to differentiate promotion methods for students from economically well-off families, middle class, or poor families.